Combating London's criminal class: a state divided, 1869-95 - Bach, Matthew (History of crime, deviance and punishment, 2020)
The origins of the habitual criminals act: 'our wretched little bill' -- Repeal and reintroduction: parliamentary debate and the question of liberty -- Registering habitual criminals: a 'salutary control'? -- Police supervision of the criminal class: a spy system -- Sentencing repeat offenders: leniency and severity in the late nineteenth century.